Unconventional warfare - Fraser, C. A. (Koers, 1968)
The world of today can look back at some fifty years of widespread and virtually continuous political revolution. Prob ably more governments have come into being, passed through drastic change, or ceased to exist than in any comparable period in history. Certainly a larger proportion of the world’s popula tion has been involved in and has been aware of these upheavals than was ever the case in earlier days. It is the political pheno menon of the twentieth century, the visible wind of revolution, stirring in many continents.